Promoting help-seeking in response to symptoms amongst primary care patients at high risk of lung cancer: a mixed method study - Wagland, Richard; Brindle, Lucy; Ewings, Sean; James, Elizabeth; Moore, Mike; Rivas, Carol; Esqueda, Ana Ibanez; Corner, Jessica (Public Library of Science, 2016)
Background: Lung cancer symptoms are vague and difficult to detect. Interventions are needed to promote early diagnosis, however health services are already pressurised. This study explored symptomology and help-seeking behaviours of primary care patients at ‘high-risk’ of lung cancer (≥50 years old, recent smoking history), to inform targeted interventions. Methods: Mixed method study with patients at eight general practitioner (GP) practices across south England. Study incorporated: postal symptom questionnaire; clinical records review of participant consultation behaviour 12 months pre- and post-questionnaire; qualitative participant interviews (n = 38) with a purposive sample. Results: A small, clinically relevant group (n = 61/908, 6.7%) of primary care patients was identified who, despite reporting potential symptoms of lung cancer in questionnaires, had not consulted a GP ≥12 months. Of nine symptoms associated with lung cancer, 53.4% (629/1172) of total respondents reported ≥1, and 35% (411/1172) reported ≥2. Most participants (77.3%, n = 686/908) had comorbid conditions; 47.8%, (n = 414/908) associated with chest and respiratory symptoms. Participant consulting behaviour significantly increased in the 3-month period following questionnaire completion compared with the previous 3-month period (p = .002), indicating questionnaires impacted upon consulting behaviour. Symptomatic non-consulters were predominantly younger, employed, with higher multiple deprivation scores than their GP practice mean. Of symptomatic non-consulters, 30% (18/61) consulted ≤1 month post-questionnaire, with comorbidities subsequently diagnosed for five participants. Interviews (n = 39) indicated three overarching differences between the views of consulting and non-consulting participants: concern over wasting their own as well as GP time; high tolerance threshold for symptoms; a greater tendency to self-manage symptoms. Conclusions: This first study to examine symptoms and consulting behaviour amongst a primary care population at ‘high- risk’ of lung cancer, found symptomatic patients who rarely consult GPs, might respond to a targeted symptom elicitation intervention. Such GP-based interventions may promote early diagnosis of lung cancer or other comorbidities, without burdening already pressurised services.